PEMANFAATAN APLIKASI SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN DAERAH RAWAN BANJIR KECAMATAN JATIASIH KOTA BEKASI - Bahar, Syairul; Fahmi, Fauzi (Jurnal Spasial, 2024)
This study aims to determine the spatial distribution of flood vulnerability levels in Jatiasih sub-district, Bekasi city. Data processing in determining flood-prone areas in Jatiasih district is carried out using the scoring method. The score  for each parameter is then summed using the field calculator in the ArcGIS 10.8 application. The parameters that used in the preparation of the flood hazard map are soil texture and type, slope, and land use. Furthermore, these parameters are overlaid (overlay) to obtain a map of flood-prone areas. the results of the analysis using the scoring method and the overlay method get the distribution of flood areas consisting of 3 classifications, namely a low flood vulnerability level of 192 ha or 8% of the sub-district area, a medium flood vulnerability level of 2111 ha or 83% of the sub-district area, and a high level of flood vulnerability cell height; area of 235 ha or 9% of the sub-district area. The points in flood areas that experience a high level of vulnerability include TNI AL housing, Kemang IFI Graha, IKIP Lecturer housing, Nasio housing, Griya Jatisari housing, Buana Risma Jatiluhur Complex, Asabri housing, Jatirasa housing, Pondok Mitra Lestari, Pondok Gede Permai housing, Nusapala housing, Jatisari camping ground, and Cahaya Kemang Permai housing.